Leptosphaeria maculans Alters Glucosinolate Accumulation and Expression of Aliphatic and Indolic Glucosinolate Biosynthesis Genes in Blackleg Disease-Resistant and -Susceptible Cabbage Lines at the Seedling Stage - Robin, Arif Hasan Khan; Laila, Rawnak; Abuyusuf, Md.; Park, Jong-In; Nou, Ill-Sup (Frontiers in Plant Science, 2020)
The fungal pathogen, Leptosphaeria maculans causes a severe and economically important disease to Brassica crops globally, well-known as blackleg. Besides, the anti-oxidative defense response of glucosinolates to fungal pathogens is widely established. Despite notable importance of glucosinolates in blackleg disease resistance the association of glucosinolate pathway genes in glucosinolate mediated defense response after L. maculans infection remains incompletely understood. The current study was designed to identify glucosinolate-biosynthesis specific genes among the eight selected candidates induced by L. maculans and associated alterations in glucosinolate profiles to explore their roles in blackleg resistance at the seedling stage of cabbage plants. The defense responses of four cabbage inbred lines, two resistant and two susceptible, were investigated using two L. maculans isolates, 03–02s and 00–100s. Pathogen-induced glucosinolate accumulation dynamically changed from two days after inoculation to four days after inoculation. In general, glucosinolate biosynthetic genes were induced at 24 h after inoculation and glucosinolate accumulation enhanced at two days after inoculation. An increase in either aliphatic (GIB, GRA) or indolic (GBS and MGBS) glucosinolates was associated with seedling resistance of cabbage. Pearson correlation showed the enhanced accumulation of MGBS, GBS, GIB, GIV and GRA after the inoculation of fungal isolates was associated with expression of specific genes. Principal component analysis separated two resistant cabbage lines – BN4098 and BN4303 from two susceptible cabbage lines – BN4059 and BN4072 for variable coefficients of disease scores, glucosinolate accumulation and expression levels of genes. Enhanced MGBS content against both fungal isolates, contributing to seedling resistance in two interactions- BN4098 × 03-02s and BN4303 × 00-100s and enhanced GBS content only in BN4098 × 03-02s interaction. Aliphatic GRA took part in resistance of BN4098 × 00-100s interaction whereas aliphatic GIB took part is resistance of BN4098 × 03-02s interaction. Aliphatic GIV accumulated upon BN4098 x 03-02s interaction but GSL-OH–Bol033373 and CYP81F2-Bol026044 showed enhanced expression in BN4303 x 03-02s interaction. The association between the selected candidate genes, corresponding glucosinolates, and seedling resistance broaden the horizon of glucosinolate conciliated defense against L. maculans in cabbage seedlings.